Pengaruh kepemimpinan transformatif terhadap perilaku loyalitas pegawai Direktorat Jenderal Perbendaharaan - Eko Dwiyanto; Aryana Satrya; Etty Puji Lestari (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
In terms of achievement, DJPb performance over the last few years in terms of public services has been good, but there is a downward trend in performance in 2020. This decline is often related to the condition of employee performance which also tends to decline, especially during the Covid-19 pandemic. This study aims to analyze the effect of transformational leadership and public service motivation to organizational citizenship behavior with job satisfaction as a mediating variable. The respondents of this study were 200 public sector employees at the regional office of the Directorate General of Treasury of DKI Jakarta Province and the Jakarta State Treasury Service Office I to VII, with the level of office are implementers/staff and functional officers. This research is quantitative with the method of collecting data through online questionnaires and processed and analyzed using Structural Equation Modeling. The results show that transformational leadership, public service motivation, and job satisfaction have a positive and significant influence on organizational citizenship behavior. In addition, it is also known that job satisfaction is able to become a mediating variable with partial criteria which further strengthens the relationship between research variables.